Genetic Instability of a Polydactyl Hypopigmented Cat With Squamous Cell Carcinoma—A Case Report - Arellano-García, María Evarista; Izaguirre-Pérez, Marian Eliza; Molina-Noyola, Leonardo Daniel; Castañeda-Yslas, Idalia Yazmín; Luna-Vázquez-Gómez, Roberto; Torres-Bugarín, Olivia (Frontiers in Veterinary Science, 2020)
Polydactyly, hypopigmentation, and squamous cell carcinoma are common in cats. However, a cat exhibiting all of these conditions has not yet been reported. This study presents the case of a 14- year-old male Mexican cat, hypopigmented, with supernumerary fingers, two preaxial and one on each posterior limb, admitted to the clinic with a lesion in the left periocular region. The cat was subjected to a general physical examination, blood, and urine chemistry, as well as a biopsy and genomic instability assessment with an analysis of the red blood cells (RBC) micronucleated erythrocytes (RBC-MNE) in the peripheral blood. The biopsy was positive for squamous cell carcinoma, and the RBC-MNE count (8.6 MNE/1000 erythrocytes) was high compared to that previously described in other domestic cats or wild cats. Thus, the genomic instability of the RBC-MNE could be used as an indicator to identify clinical conditions of felines, particularly those with one of the characteristics exhibited by this Mexican cat. The RBC-MNE test is the most widely used in the world for the evaluation of DNA damage, but to our knowledge, it has not been used to identify vulnerable non-human specimens.